Estudio comparativo de la actividad antioxidante, antinflamatoria, antimicrobiana de extractos orgánicos de planta silvestre y cultivos in vitro de Ludwigia octovalvis (Jacq.) P.H. Raven - Tadeo Cuenca, Stephany Abigail (Universidad Autónoma Metropolitana, 2024)
Ludwigia octovalvis is an herb of the Onagraceae family used in Mexico, particularly in the states of Morelos, Veracruz, and Oaxaca, to treat multiple skin conditions, infections, dysuria, and diabetes, among other things. Previous studies have shown its potential as an anti-diabetic, antimicrobial, and antioxidant. However, although many Mexican medicinal plants are widely used, only a tiny percentage have been studied pharmacologically and most are collected from the wild without a sustainability plan. The in vitro cultivation of L. octovalvis is presented as an alternative to propagating the plant in a controlled manner, without risk of extinction, and to obtain pharmacological compounds under stable conditions. This study aims to evaluate and compare the antioxidant, anti-inflammatory, and antimicrobial activity of extracts from the wild plant, in vitro cultured seedlings, and callus cultures to determine the conditions that maximize the production of bioactive compounds. Callus cultures were initiated on MS basal medium supplemented with different concentrations of naphthalene acetic acid (NAA) or 2,4-dichlorophenoxyacetic acid (2,4-D) combined with 6-benzylaminopurine (BAP) or kinetin (KIN). In vitro germinated seedlings were used to source two types of explants: leaf and stem. Two morphogenic responses were obtained from these treatments: organogenesis (direct and indirect) and callogenesis. With the combination of 0.1 mg/L BAP + 1 mg/L NAA and the stem explant, seedlings were obtained by indirect organogenesis, which showed morphological differences concerning those grown without phytohormones. A callus culture line was established with the leaf explant using 1 mg/L BAP + 0.1 mg/L 2,4-D, achieving maximum biomass and bioactive compounds production after six weeks. Extracts were obtained from these in vitro cultures by maceration with n-hexane, ethyl acetate, and methanol at room temperature. Free radical scavenging of the different extracts was measured using the DPPH assay. The extracts were subjected to antimicrobial screening against methicillin-resistant Staphylococcus aureus (MRSA), S. aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans by disc diffusion and broth microdilution. Anti-inflammatory activity was evaluated using a murine biological model of TPA-induced atrial inflammation in male and female CD1 mice. The phytochemical components of the extracts were identified by gas chromatography coupled with mass spectrometry (GC-MS). The extracts with the highest uptake of the free radical DPPH were the ethyl acetate extract of the seedling (91.4%) and the methanolic extract of the callus (85.3%). At a 50 mg/mL concentration, the hexane and methanol extracts of callus and seedling formed inhibition halos against S. aureus of 16.07 ± 1.30 and 8.39 ± 1.47 mm, respectively. Almost all extracts tested showed activity against MRSA; in particular, the seedling hexane extract showed a MIC of 31.25 µg/mL, the wild plant ethyl acetate extract 62.5 µg/mL, and the callus methanol extract 250 µg/mL. No activity against E. coli, P. aeruginosa, and C. albicans was detected in the tested extracts. The ethyl acetate extract at 0.5 mg/eye showed superior anti-inflammatory activity than indomethacin at the same dose, with edema inhibition of 27.96% (males) and 22.34% (females). Twenty-five compounds were found in seedling and callus extracts, including α-tocospiro B, α-tocopherol, n-hexadecanoic acid, oleic acid, palmitoleic acid, saffron, betulin, betulinaldehyde, campesterol, stigmasterol, phytol, γ-sitosterol, γ-tocopherol, lupeol and β-sitosterol. The in vitro cultures produced different compounds from those reported for the wild plant; however, several of these are relevant for their pharmacological properties, suggesting that in vitro culture may be an effective alternative to produce bioactive metabolites. These results highlight the potential of biotechnology in cultivating L. octovalvis for pharmaceutical applications and the need for further research to optimize cultivation conditions and maximize the production of beneficial compounds.; Ludwigia octovalvis es una hierba de la familia Onagraceae que se utiliza en México, especialmente en los estados de Morelos, Veracruz y Oaxaca, para tratar diversas afecciones cutáneas, infecciones, disuria y diabetes, entre otras. Estudios previos han demostrado su potencial como antidiabético, antimicrobiano y antioxidante. Sin embargo, aunque muchas plantas medicinales mexicanas se utilizan ampliamente, solo un pequeño porcentaje ha sido estudiado farmacológicamente, y la mayoría se extrae de la naturaleza sin un plan de sostenibilidad. El cultivo in vitro de L. octovalvis se presenta como una alternativa para propagar la planta de manera controlada y sin riesgos de extinción, permitiendo obtener compuestos farmacológicos en condiciones estables. El objetivo de este estudio es evaluar y comparar la actividad antioxidante, antiinflamatoria y antimicrobiana de extractos de la planta silvestre, plántulas cultivadas in vitro y cultivos de callo, con el fin de determinar las condiciones que maximizan la producción de compuestos bioactivos. Los cultivos de callo se iniciaron en medio basal MS, adicionado con concentraciones variables de ácido naftalenacético (ANA) o ácido 2,4-diclorofenoxiacético (2,4-D), combinados con 6-bencilaminopurina (BAP) o kinetina (KIN). Se utilizaron plántulas cultivadas in vitro como fuente de dos tipos de explantes: hoja y nodo. A partir de estos tratamientos, se obtuvieron dos respuestas morfogénicas: organogénesis (directa e indirecta) y callogénesis. Con la combinación de 0.1 mg/L BAP + 1 mg/L ANA y el explante de nodo, se obtuvieron plántulas por organogénesis indirecta, las cuales presentaron diferencias morfológicas con respecto a las que crecieron sin fitohormonas. Se estableció una línea de cultivo de callos con el explante de hoja utilizando 1 mg/L BAP + 0.1 mg/L 2,4-D, logrando una producción máxima de biomasa y compuestos bioactivos en la semana seis. A partir de estos cultivos in vitro, se obtuvieron extractos mediante maceración a temperatura ambiente con n-hexano, acetato de etilo y metanol. La eliminación de radicales libres de los diferentes extractos se midió utilizando el ensayo DPPH. Los extractos se sometieron a un cribado antimicrobiano contra Staphylococcus aureus resistente a la meticilina (SARM), S. aureus, Escherichia coli, Pseudomonas aeruginosa y Candida albicans, mediante difusión en disco y microdilución en caldo. La actividad antiinflamatoria se evaluó utilizando un modelo biológico murino de inflamación auricular inducida por TPA en ratones CD1, tanto machos como hembras. Los componentes fitoquímicos de los extractos se identificaron mediante cromatografía de gases acoplada a espectrometría de masas (CG-EM). Los extractos que mostraron mayor captación del radical libre DPPH fueron el extracto de acetato de etilo de plántula (91.4%) y el extracto metanólico de callo (85.3%). A la concentración de 50 mg/mL, los extractos de hexano de callo y metanol de plántula formaron halos de inhibición contra S. aureus de 16.07 ± 1.30 y 8.39 ± 1.47 mm, respectivamente. Casi todos los extractos evaluados exhibieron actividad frente al SARM; en particular, el extracto de hexano de plántula mostró una CMI de 31.25 µg/mL, el extracto de acetato de etilo de la planta silvestre de 62.5 µg/mL, y el extracto metanólico de callo de 250 µg/mL. No se detectó actividad contra E. coli, P. aeruginosa y C. albicans en los extractos evaluados. El extracto de acetato de etilo a 0.5 mg/oreja mostró una actividad antiinflamatoria superior a la indometacina a la misma dosis, con una inhibición del edema de 27.96% (machos) y 22.34% (hembras). Se encontraron 25 compuestos en los extractos de plántula y callo, entre ellos: α-tocospiro B, α-tocoferol, ácido n-hexadecanoico, ácido oleico, ácido palmitoleico, azafrina, betulina, betulinaldehído, campesterol, estigmasterol, fitol, γ-sitosterol, γ-tocoferol, lupeol y β-sitosterol. Los cultivos in vitro produjeron compuestos diferentes que a los reportados para la planta silvestre; no obstante, varios de estos son relevantes por sus propiedades farmacológicas, lo que sugiere que el cultivo in vitro puede ser una alternativa eficaz para la producción de metabolitos bioactivos. Estos hallazgos destacan el potencial de la biotecnología en el cultivo de L. octovalvis para aplicaciones farmacéuticas y la necesidad de continuar con investigaciones para optimizar las condiciones de cultivo y maximizar la producción de compuestos beneficiosos.